Teak Leaf Tea Product Development in Kebontunggul Village, Mojokerto - Kok, Tjie; Puspitasari, Elia Devina; Madjid Abdillah, Abdul; Pramesti, Nertico Hana; Sutanto, Tiffany Arista; De Jesus, Graciana Alves; Kresna Darmasetiawan, Noviaty; Mustikasari, Hany; Widyaastuti, Endang Widoeri; Felita, Carissa; Vania, Margaretha (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Kebontunggul Village in Mojokerto, with its abundant natural resources, has a golden opportunity to develop into an herbal village. The fertile land in this village serves as a habitat for teak plants, producing leaves rich in bioactive compounds. A collaboration between the University of Surabaya, Widya Mandala Surabaya Catholic University, Village-owned Enterprises, the Tourism Awareness Group, and the Family Welfare and Empowerment Organization, facilitated by the Ministry of Education and Culture, processed the teak leaves into powder and tea. This collaboration aimed to improve public health and open up economic opportunities for the local community. The process included socialization, training, and evaluation, with the Participation Rural Appraisal (PRA) method employed to ensure active community participation at every stage, from identifying the potential of natural resources to the production and marketing of the products. As a result, the village has successfully produced teak leaf powder and teak leaf tea, which have started to be commercialized.